(3cTa GdZeI Yf HUGFQ GdCFeIs - (3YHO Gddg, eNOhe Gdedc ` GdgfOj GdSdWGfHhQj,J (B1006 (3g` s ((3CMeO Hf Ydi Hf ESeGYjd GdCMeOi GdhGYX s)
(3ChdgG (B:s
(3RabdJ dg CJOQi ef gPG aScJ abdJ SjO GdChdjf hGdCNQjf s
(3BNQgG (B:s
(3hYdi SGFQ GdCfHjGA hGdeQSdjf hQVi Gddg Yf CUMGH QShd Gddg CLejYf hYdi GdJGHYjf dge HEMSGf Edi jhe GdOjf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs